Challenges of palliative care integration into routine hospital care in Iran: A Q-method inquiry on key healthcare providers’ prospects - Seemin Dashti; Hassan Mahmoodi; Abdolreza Shaghaghi (Health Promotion Perspectives)
Background: Inclusion of palliative care (PalC) in the routine provided healthcare of hospitals is emphasized by the World Health Organization (WHO) in the endorsed Health Promoting Hospitals (HPH) initiative. Nonetheless, an evidence gap exists about explicit barriers and operational complexities that might prevent embeddedness of PlaC in the Iranian National Healthcare System (INHS) and this was the main impetus for the conception of the current research. Methods: The Barry and Proops’ recommended Q method procedures were used in 6 phases including concourse development through the scientific literature search and consultation with the 27 key informants, statements’ selection, population set (P-set) selection, Q sorting and factor analysis. Principal component analysis and Varimax rotation were used in factor analysis and the values of factor loadings≥0.4 were considered satisfactory in assessing the degree to which a certain Q sort conforms to a particular factor. Results: The extracted four factors that accounted for 47% of the total observed variance were shortage of physical space and number of the healthcare providers (HCPs), inadequate involvement of the patient’s family members in end-of-life treatment decisions, communication barriers, and inadequate training of HCPs for PalC provision. Conclusion: This study elicited important barriers of incorporating PalC into the routine hospital care and hence, importance of taking a multifaceted approach for achieving the goals of INHS in quality healthcare provision. Contrasting views of the approached HCPs could help development of the evidence-based national policies concordant with the HPH initiative in Iran.